Prevalence of postnatal depression and associated risk factors among South Asian mothers living in a newly developing country - HASHIM AL SAYED MOHAMED,; MARYAM MOHAMED AL JABER,; ZAIDFAHIM AL-HAMADANI,; HAMZEH YOUSEF KHMOUR,; BADRYIA ABDULLA AL LENJAWI,; JOSIA MARKUS SCHLOGL, (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract Introduction Postnatal Depression (PND) is a major health problem affecting mother, her child and family. Its prevalence and associated risk factors among South Asian mothers (SAM) living in Qatar remain unknown. The objectives of this study were to estimate the prevalence of PND among (SEAM) in Qatar and to correlate risk factors contributing to the development of PND. Materials and methods A total of (285 ) (SAM)females who were six months postpartum were interviewed as part of a prospective study conducted in primary health care centers in Qatar. PND symptoms were defined as present when subjects had an Edinburgh Postnatal Depression Scale score of 10 or higher. Descriptive statistics were used for summarizing the study and outcome variables. The χ2 test and ORs with 95% confidence intervals (CIs) were used for observation and quantifying the association between different variables. Multivariate binary logistic regression was used to identify the independent associated factors of PPD. P≤0.05 was considered significant. Variables included were age , occupation, education level ,previous psychiatric history ,comorbidities , ,history of depression during current pregnancy, history of anxiety during current pregnancy, number of previous pregnancies, strong social support, husband support, marital problem before pregnancy and ongoing marital problems during current pregnancy. Results The prevalence of postnatal depression among 285 respondents was 33.2% . several psychosocial risk factors were significantly associated with postnatal depression and, after multiple regression analysis, a history of depressive illness ,anxiety ,marital problems before delivery ,a history of diabetes and asthma ,history of congenital malformations ,and lack of mother support.Other variables, including age, parity, education, occupation, and delivery type, were not significantly correlated (P=0.15–0.95), but marginally indicative of the risk of depressive symptoms. Conclusion This study showed a high rate of depressive symptoms among(SAM) six months Postpartum . Future screening protocols must be employed at primary care level and hospital based clinics in Qatar to detect and treat post natal depression. Keywords: postnatal depression, South Asians, primary health care ,Doha, EPDS